2001
DOI: 10.1128/aac.45.3.764-767.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Linezolid against Rapidly Growing Mycobacteria

Abstract: Linezolid is an oxazolidinone available as an oral drug which has activity against most gram-positive bacteria. However, few species of the genus Mycobacterium have been studied. We tested 249 clinical isolates and 10 reference strains of rapidly growing mycobacteria for susceptibility to linezolid by broth microdilution. Clinical species included the Mycobacterium fortuitum group (n ‫؍‬ 74), M. abscessus (n ‫؍‬ 98), M. chelonae (n ‫؍‬ 50), M. mucogenicum (n ‫؍‬ 10), and M. fortuitum third biovariant complex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(113 citation statements)
references
References 26 publications
(16 reference statements)
2
108
0
3
Order By: Relevance
“…Linezolid has good activity against many gram-positive anaerobes; its activity against Bacteroides fragilis is borderline (minimum inhibitory concentration of 4 g/mL for 50% of strains), but it is bactericidal against these organisms (8). Of interest, linezolid exhibits relatively good in vitro activity against many strains of Mycobacterium tuberculosis (8) and has activity against the Mycobacterium avium complex and several rapidly growing mycobacteria, including Mycobacterium fortuitum, Mycobacterium chelonae, and Mycobacterium abscessus (14,15). The clinical significance of the activity of linezolid against mycobacteria is not known, but, of interest, it is possible to produce oxazolidinone derivatives with even greater activity against mycobacteria (16).…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…Linezolid has good activity against many gram-positive anaerobes; its activity against Bacteroides fragilis is borderline (minimum inhibitory concentration of 4 g/mL for 50% of strains), but it is bactericidal against these organisms (8). Of interest, linezolid exhibits relatively good in vitro activity against many strains of Mycobacterium tuberculosis (8) and has activity against the Mycobacterium avium complex and several rapidly growing mycobacteria, including Mycobacterium fortuitum, Mycobacterium chelonae, and Mycobacterium abscessus (14,15). The clinical significance of the activity of linezolid against mycobacteria is not known, but, of interest, it is possible to produce oxazolidinone derivatives with even greater activity against mycobacteria (16).…”
Section: Spectrum Of Activitymentioning
confidence: 99%
“…Furthermore, we investigated whether LCB01-0371 had the same molecular target as the other compounds of the oxazolidinone class, such as linezolid and sutezolid (PNU-100480). Linezolid binds to the 23S subunit of the bacterial ribosome to prevent protein synthesis; in vitro testing indicated that M. abscessus was susceptible to linezolid (26). As seen in Fig.…”
Section: Lcb01-0371 Is Effective Against M Abscessusmentioning
confidence: 85%
“…La actividad in vitro de estos fármacos parece ser buena pero la experiencia clínica aún es limitada. Según nuestros resultados, tigeciclina presenta una excelente actividad para todas las especies de MCR; linezolid es efectivo frente a M chelonae, pero algo menos frente a M fortuitum y M abscessus; en el caso de quinupristina/dalfopristina, se puede decir que es ineficaz frente a la mayoría de las especies de MCR 12,18,[22][23][24] .…”
Section: N V E S T I G a C I ó Nunclassified